2019
DOI: 10.1136/bmjopen-2018-025303
|View full text |Cite
|
Sign up to set email alerts
|

Social support network typologies and their association with dementia and depression among older adults in Singapore: a cross-sectional analysis

Abstract: ObjectivesTo examine the social support network type and its associations with depression and dementia among older adults in Singapore.DesignThis study is a cross-sectional analysis of data from the Well-being of the Singapore Elderly study. The Practitioner Assessment of Network Type was used to identify five social support network types. Odds Ratios (OR) of dementia and depression were estimated with logistic regression and multinomial logistic regression, respectively, adjusted for sociodemographic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Latent profile analysis, LPA) have received growing interest in the typologies of social support networks in recent years (e.g. [21,22]). What's more, although based on slightly different concepts, some researchers have used cluster analysis to study social network typologies for a long time (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Latent profile analysis, LPA) have received growing interest in the typologies of social support networks in recent years (e.g. [21,22]). What's more, although based on slightly different concepts, some researchers have used cluster analysis to study social network typologies for a long time (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[23]). More importantly, the existing papers demonstrated different support profiles would be differently associated with mental health outcomes [21,22,24]. Specifically, Burholt et al [21] adopted LPA and found that the four social support profiles differ in their relationships to wellbeing in older migrants.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature has revealed a link between social networks and mental health outcomes, focusing mainly on middle-aged [3] or elderly people [4], or patients with mental illnesses such as depression [5][6][7][8], anxiety [9], psychosis [10], post-traumatic stress disorder [2,11,12], or dementia [13]. Social networks here refer individual's connections including with both family and close friends, or broader social ties within a community [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Social networks refer to the systems of social relationships in which individuals are connected to one another through different sets of interactions [4][5][6]. Abundant research has reported a link between social networks and mental health outcomes in both positive and negative ways [7,8], in middle-aged [9] or elderly people [10], in Western [11][12][13] or non-Western background [6,14,15], or patients with mental illnesses such as depression [3,[16][17][18], anxiety [19], psychosis [20], post-traumatic stress disorder [8,21,22], or dementia [14]. Some researchers have proposed that an inadequacy of social network quality or quantity may lead to loneliness, which is related to an elevated risk of depression or psychiatric symptoms [16,23,24].…”
Section: Introductionmentioning
confidence: 99%